Implementation of GPS Spoofing Test Environment using Multiple GPS Simulators - So, Hyoungmin (Journal of Positioning, Navigation, and Timing, 2016)
A Global Navigation Satellite System (GNSS), which is typically exemplified by the Global Positioning System (GPS), employs a open signal structure so it is vulnerable to spoofing electronic attack using a similar malicious signal with that used in the GPS. It is necessary to require a spoofing test evaluation environment to check the risk of spoofing attack and evaluate the performance of a newly developed anti-spoofing technique against spoofing attacks. The present paper proposed a simulation method of spoofing environment based on simulator that can be implementable in a test room and analyzed the spoofing simulation performance using commercial GPS receivers. The implemented spoofing simulation system ran synchronized two GPS simulator modules in a single scenario to generate both of spoofing and GPS signals simultaneously. Because the signals are generated in radio frequency, a commercial GPS receiver can be tested using this system. Experimental test shows the availability of this system, and anti-spoofing performance of a commercial GPS receiver has been analyzed. KCI Citation Count: 0